Caffeic acid ester derivatives and flavonoids of genus Arnaldoa (Asteraceae, Barnadesioideae). (October 2019) - Ccana-Ccapatinta, Gari V.; Ferreira, Paola L.; Groppo, Milton; Da Costa, Fernando B.
Abstract: The phytochemical composition of Arnaldoa species is barely known. In this work, the occurrence of caffeic acid ester derivatives and flavonoids in A. argentea, A. macbrideana and A. weberbaueri was established by liquid chromatography associated to high-resolution mass spectrometry analyses and comparison with data from isolated compounds. The distribution of chlorogenic acids in the genus Arnaldoa is herein described for the first time. The metabolite profile of Arnaldoa species was compared to that of Tithonia diversifolia, a known and rich source of chlorogenic acids and sesquiterpene lactones. In addition to the mono- and dicaffeoyl quinic acids present in T. diversifolia, Arnaldoa species exhibited the mono- and dicaffeoyl tartaric acids. Furthermore, mass features correspondent to that of sesquiterpene lactones present in T. diversifolia were not observed in Arnaldoa species. The chemotaxonomic implications of caffeic acid ester derivatives and flavonoid glycosides, as well as the potential absence of sesquiterpene lactones in the genus Arnaldoa and subfamily Barnadesioideae are discussed. Highlights: Seven compounds were isolated from an alcoholic extract of Arnaldoa weberbaueri. Tithonia diversifolia was used as a surrogate standard for profiling chlorogenic acids in Arnaldoa species. The occurrence of chlorogenic acids in the genus Arnaldoa is described for the first time.